IMPROVING SELF-DEVELOPMENT COMPETENCY OF FUTURE PRIMARY CLASS TEACHERS - Abdullayeva, Barno Sayfutdinovna; Aliyev, Nurillo Abdiqayumovich; Ergasheva, Durdona Safarali qizi (Educational Research in Universal Sciences, 2022)
Personal development is a powerful tool to reach a well-defined and healthy sense of self as teachers, i.a, self-concept enhancement, which can result in positive self-esteem and self-confidence. Besides, it enables teachers to recognize, understand and manage their emotions thereby having good intrapersonal skills and the article also reflected on these.